Prevalence of Infection and Changing Pattern of Organisms Causing Infections in Childhood Nephrotic Syndrome - Mahmud, KM Sarwar; Rana, Rubina Afroz (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Infection remains an important complication of children with nephrotic syndrome. It results in significant morbidity and may also be responsible for a poor response to steroid therapy or induce relapse in child who has already attained remission. Objectives: This study was conducted to find out pattern of infection and type of organisms causing infections in nephrotic syndrome. Methods: This cross sectional study was conducted in the Paediatric Nephrology Department of Dhaka Shishu (Children) Hospital from January 2010 to November 2010. One hundred fifteen (115) cases of nephrotic syndrome, age between 1 to 13 years were enrolled according to the inclusion criteria. Along with routine investigations, urine, blood and throat swab culture and sensitivity and MT test were done. Risk factors of infection were also determined. Statistical analysis was done by SPSS version 12. Level of significance was taken as <0.05. Results: Prevalence of infection in nephrotic syndrome was 54.78%. Infections were more common in childhood nephrotic syndrome below 6 years of age. Infections encountered in nephrotic syndrome were UTI 51(44.34%), septicemia 4(3.47%), pneumonia 5(4.34%), peritonitis 1(0.87%), cellulitis 1(0.87%) and tuberculosis 1(0.87%). Statistically significant risk factors associated with infection were generalized edema, steroid dependence, steroid resistance, persistent proteinuria and high spot urine protein creatinine ratio. In case of UTI E. coli was the commonest 27(52.9%) organism followed by Morganella and Pseudomonas 5(9.8%). Conclusion: Prevalence of infection in nephrotic syndrome is very high and E. coli is the commonest organism found in this study. Generalized edema, persistent proteinuria, hypoalbuminemia, steroid dependence, steroid resistance are important risk factors for infection. DS (Child) H J 2021; 37(1): 28-33